Hyperspectral imaging for perioperative monitoring of microcirculatory tissue oxygenation and tissue water content in pancreatic surgery: an observational clinical pilot study - Dietrich, Maximilian; Marx, Sebastian; Forst, Maik von der; Bruckner, Thomas; Schmitt, Felix; Fiedler-Kalenka, Mascha; Nickel, Felix; Studier-Fischer, Alexander; Müller, Beat P.; Hackert, Thilo; Brenner, Thorsten; Weigand, Markus A.; et al. (Perioperative medicine, 2021)
Hyperspectral imaging (HSI) could provide extended haemodynamic monitoring of perioperative tissue oxygenation and tissue water content to visualize effects of haemodynamic therapy and surgical trauma. The objective of this study was to assess the capacity of HSI to monitor skin microcirculation and possible relations to perioperative organ dysfunction in patients undergoing pancreatic surgery.
Gesehen am 22.12.2021